Hard to Swallow: Scaling Relationships Between the Size of Avian Prey and the Overall Size and Maximal Gape of Brown Treesnakes - Shane R. Siers; Juan‐Carlos Mungaray; Martin Kastner; Bruce C. Jayne (Ecology and Evolution, 2025)
ABSTRACT Snakes are a useful model for gaining insights into the relationships between predator and prey sizes and resource utilization because their anatomy limits the size of prey that can be swallowed whole. However, data are sparse regarding how commonly gape‐limited predators eat or attempt to eat prey with sizes up to or exceeding their maximal gape. Thus, for an invasive predator, the brown treesnake (Boiga irregularis), we fed captive snakes dead birds with an extremely large range (17%–447%) of relative prey area (RPA = prey cross‐sectional area/snake gape area) to test the predictive value of RPA for snakes attempting to ingest or successfully ingesting prey. As expected, RPA significantly predicted (logistic regression p < 0.0001) the probability of birds being eaten, with an upper size limit similar to the maximal gape of the snakes. Although RPA also significantly predicted (p = 0.003) the probability of attempting to eat a bird, it was less accurate in predicting attempts than successes, and many snakes attempted to eat birds too large to swallow. Twenty‐five snakes attempted to eat birds with RPA ranging from 130% to 447%. The longest durations of unsuccessful feeding attempts were often for values of RPA near 100% rather than the extremely large values. For six large birds with mean measured RPA = 93%, the prey diameter soon after ingestion averaged 14% less than that measured prior to ingestion, which can allow snakes to consume 30% more mass than would otherwise be possible. Our findings complement a recent field study that concluded brown treesnakes regularly attempt to eat live birds too large to swallow. Our results also greatly expanded the known range of avian prey sizes that these snakes attempt to eat. Consequently, brown treesnakes pose a risk to birds with sizes well beyond the limit on prey size imposed by gape.